2020
DOI: 10.1128/mcb.00366-18
|View full text |Cite
|
Sign up to set email alerts
|

AKT Regulates Mitotic Progression of Mammalian Cells by Phosphorylating MASTL, Leading to Protein Phosphatase 2A Inactivation

Abstract: Microtubule-associated serine/threonine kinase like (MASTL), also known as Greatwall (Gwl) kinase, has an important role in the regulation of mitosis. By inhibiting protein phosphatase 2A (PP2A), it plays a crucial role in activating one of the most important mitotic kinases, known as cyclin-dependent kinase 1 (CDK1). MASTL has been seen to be upregulated in various types of cancers and is also involved in tumor recurrence. It is activated by CDK1 through phosphorylations in the activation/T-loop, but the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Exogenous overexpression of MASTL triggers AKT activation in an ENSA/PP2A-independent manner ( Rogers et al., 2018 ; Vera et al., 2015 ). In addition, AKT-mediated proliferation in colorectal cell lines can be attenuated by MASTL silencing ( Reshi et al., 2020 ). Our results show that silencing of MASTL leads to a significant decrease in TGFBR2 levels and TGF-β-induced PI3K-AKT activation.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous overexpression of MASTL triggers AKT activation in an ENSA/PP2A-independent manner ( Rogers et al., 2018 ; Vera et al., 2015 ). In addition, AKT-mediated proliferation in colorectal cell lines can be attenuated by MASTL silencing ( Reshi et al., 2020 ). Our results show that silencing of MASTL leads to a significant decrease in TGFBR2 levels and TGF-β-induced PI3K-AKT activation.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that changes in the subunit composition, localization, and activity of PP2A by PyST may affect some critical cellular activities, including mitotic regulation. PP2A is known to be extremely important at the entry as well as exit of mitosis (54)(55)(56)(57). Deregulation of PP2A activity in actively dividing cells therefore leads to severe abnormalities during mitosis, as is clearly visible in PyST-expressing cells also, leading to the activation of the spindle assembly checkpoint (SAC).…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, possible that MASTL may influence AKT signaling differentially in cycling (Vera et al , 2015) or starved/G0 cells as suggested by our data. Interestingly, AKT may lead to MASTL phosphorylation and activation specifically during mitosis (Reshi et al , 2020), although whether this is mediated by direct phosphorylation and whether these data have any relevance in vivo in a physiological context have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%